2013
DOI: 10.19030/cier.v6i2.7731
|View full text |Cite
|
Sign up to set email alerts
|

A Survey Of Professor Acceptance And Use Of E-Textbooks In Higher Education

Abstract: As electronic books (e-books) have continued to gain in popularity, more and more books are becoming available in electronic format. Textbooks are no exception. More and more publishers are making textbooks available in electronic format (e-textbooks). There have been many devices specifically designed to use e-books and e-textbooks with many more devices which utilize e-book apps to further increase the availability and ease of moving to e-books. Many professors are embracing the new technology, but others ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Granted, the introduction of different options for provision and access of resources for students is not necessarily straightforward. As Brown (2013) notes when commenting upon the use of e-textbooks, as one possibility of an alternative to hard copy textbooks, "just because we can do something does not mean we should" (p. 220).…”
Section: Discussionmentioning
confidence: 99%
“…Granted, the introduction of different options for provision and access of resources for students is not necessarily straightforward. As Brown (2013) notes when commenting upon the use of e-textbooks, as one possibility of an alternative to hard copy textbooks, "just because we can do something does not mean we should" (p. 220).…”
Section: Discussionmentioning
confidence: 99%
“…Faculty appreciated having portable access to content, electronic citations and digital images, yet felt unsure of the technological capabilities of the e‐textbook platform and indicated a desire for increased assistance and support for its use. Brown also surveyed professor acceptance and use of e‐textbooks in higher education and found similar sentiments; he acknowledged that there is limited instructor experience with the use of e‐textbooks and their preference continues to remain with printed textbooks. Platform components such as searching and cross‐referencing were seen by students and faculty as convenient features; however, many cited physical strain, notably eye strain, with the associated increase in screen time.…”
Section: Discussionmentioning
confidence: 87%
“…The authors recognized that although there is a shift in dental education towards online textbooks, their students did not support the change. 21 Many institutions of higher education have started adopting the use of electronic textbooks in their programming, 6,[26][27][28] and similar to attitudes identified in students, faculty have met the shift with mixed perceptions. In a study conducted by Stein et al, 26 results revealed that faculty both supported and hesitated in their adoption of electronic textbooks.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a study conducted in Japan in 2015 reported that the share of e-titles in Japanese book market was only 6% [7]. Brown [8] claims that, although e-books are gaining popularity, their acceptance is not yet universal. A study of teenage female students in Singapore showed that 82.5% of them preferred print books for leisure reading [9].…”
Section: Literature Reviewmentioning
confidence: 99%